Imunološki testi in odkrivanje okužbe z bakterijo Helicobacter pylori - Kotnik, Vladimir (Zdravniški vestnik, 2011)
Background: Herewith we present the results of four-year testing, and more than ten years of experience in laboratory determination and interpretation ofHelicobacter pylori (Hp) infection. An analysis was performed to draw attention of the physicians to the value and importance of immunological testing for the recognition of Hp infection. Methods: Serum and plasma sampleswere tested using conventional ELISA test, and stool samples using Hp antigen stool test. Results: We found that in 33.85 % of 446 samples specific antibodies of IgG class were confirmed, specific antibodies of IgA class were found in 5.38 %, and antigen in stool was found in 21.21 % of 246 samples. Thetest for the detection of specific IgG antibodies was repeated after the treatment in eight patients, for IgA antibodies never and for antigen in stoolin seven patients. None of the patients had a sample of blood and stool taken and sent simultaneously. All the patients in whom testing was repeated, presented with a decrease in the amount of antibodies and absence of antigen in the stool, verifying that the curative treatment was successful. Conclusions: In the conclusion of the analysis we reveal that the doctors in our country rarely use immunological tests in the diagnostic procedure for thedetection of Hp infection. If they are using them, they do not control the obtained results adequately, which is not correct! The presented situation is the consequence of the availability of sophisticated diagnostic procedures in the framework of university hospitals.
Keywords: bakterijske infekcije; Helicobacter pylori; imunski testi; serološka diagnostika; želodčne bolezni